Welfare and performance of the animal production: a systematic review (Research, Society and Development, 2022)
When we refers to animals of production, the considerations that involve knowledge about the behavior of these animals are even more evident, since in addition to impacting their development, it impacts society as a whole and ends up also impacting the economy. of the country, since these animals will provide society with products rich in protein of high biological value, which are essential for the fullness of human beings' quality of life. The proteins of animal origin most commercialized and consumed by human beings come from pigs, poultry, cattle, but as the final product from their creation is directly related to the management during the creation of the animals, and this is related to the behavior of the animals. Animals, which in turn is a decisive variable in the consumption of products by humans, animal husbandry systems must be allied to animal welfare, the latter being closely associated with the understanding of natural habits related to each species and animal category to be produced. However, not all agents of society, whose work culminates in the production of food of animal origin, have the knowledge and know how to proceed to monitor this issue closely. In this sense, the objective was to systematically investigate how production systems interfere with the performance of production animals and how management can affect stress levels and welfare.